If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(w + 7) + 17 = 11 Reorder the terms: -2(7 + w) + 17 = 11 (7 * -2 + w * -2) + 17 = 11 (-14 + -2w) + 17 = 11 Reorder the terms: -14 + 17 + -2w = 11 Combine like terms: -14 + 17 = 3 3 + -2w = 11 Solving 3 + -2w = 11 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2w = 11 + -3 Combine like terms: 3 + -3 = 0 0 + -2w = 11 + -3 -2w = 11 + -3 Combine like terms: 11 + -3 = 8 -2w = 8 Divide each side by '-2'. w = -4 Simplifying w = -4
| X-(-4)/6=-5 | | 4x/2=1715 | | 2750=25(9+35) | | -1+5=2(-5+1) | | 18x/45 | | 5+5=2(10+1) | | 18=45 | | 10/52=x/25 | | 4a+15=3 | | 155+8y-65+y=180 | | 2y+16x=96 | | (x+5)(x)=72 | | -(k-7)=0 | | 169x^2-169x+360=0 | | 2secx-3cosx=0 | | 905=5(x+19) | | 2x+16y+84=180 | | 6-j=2 | | 1.5m-3.6=2.4 | | 1.5-3.6=2.4 | | F(x)=6(2.5)x | | 1=4-s | | 38x+2+2x+8=90 | | X=1.4+0.8x | | 15=3+3h | | Y=15(0.5)x | | 15u=-14 | | 38x+2=2x+8 | | 7x-3=12x-22 | | X+(x+1)-16=56 | | 7-x=8x-12 | | (5u+9)(3+u)=0 |